2022
DOI: 10.1155/2022/3861092
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Diagnostic Value of Endocan in Kidney Diseases

Abstract: Endocan, previously called endothelial cell-specific molecule-1, is a soluble proteoglycan that is predominantly expressed in vascular endothelial cells of the lungs and kidneys. It is upregulated by proinflammatory cytokines and plays a critical role in inflammatory, proliferative, and neovascularization processes. The utility of endocan as a biomarker in a wide spectrum of diseases is being increasingly acknowledged. In this review, we summarize the current evidence concerning the role of endocan in kidney d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
4
0
2
Order By: Relevance
“…Recent data have confirmed the importance of endocan in inflammation, vascular proliferation, and neogenesis[ 22 ]. In human umbilical vein endothelial cells under intermittent hypoxia, endocan promotes the expression of the cell adhesion molecule slCAM1.…”
Section: Discussionmentioning
confidence: 91%
“…Recent data have confirmed the importance of endocan in inflammation, vascular proliferation, and neogenesis[ 22 ]. In human umbilical vein endothelial cells under intermittent hypoxia, endocan promotes the expression of the cell adhesion molecule slCAM1.…”
Section: Discussionmentioning
confidence: 91%
“…In the literature, recent studies showed that endocan values were affected in many diseases such as kidney diseases, 38 T2DM, 39,40 preterm premature rupture of membrane, 41 preeclampsia, 42 non‐alcoholic fatty liver disease, 43 cancer, 44 periodontal disease, 45 and human obesity 46 in which vascular angiogenesis, endothelial dysfunction, and inflammation was claimed to be the underlying pathophysiology. The fact is that endocan is an important biomodulator that presents in complicated pregnancies, probably due to the potential role of regulating insulin resistance, like the association shown with T2DM formerly.…”
Section: Discussionmentioning
confidence: 99%
“…In CKD, elevated levels of endocan were observed compared to the control group, and the concentration of endocan positively correlated with the CKD stage while negatively correlated with the estimated glomerular filtration rate [6]. Additionally, higher levels of endocan were noted in CKD patients with cardiovascular disease (CVD) than in those without CVD [36]. In hemodialysis, patients with higher endocan levels were found to have more frequent CV events, lower BMI, and lower serum TG and albumin levels [18].…”
Section: Discussionmentioning
confidence: 99%